Butanol production from thin stillage using Clostridium pasteurianum - Ahn, Jae-Hyung; Sang, Byoung-In; Urn, Youngsoon (ELSEVIER SCI LTD, 2011)
The production of butanol from thin stillage by Clostridium pasteurianum DSM 525 was evaluated in the paper. At initial pH values ranging from 5.0 to 7.0 C pasteurianum DSM 525 produced 6.2-7.2 g/L of butanol utilizing glycerol in thin stillage as the main carbon source, with yields of 0.32-0.44 g butanol produced/g glycerol consumed, which are higher than previously reported yields (e.g., 0.14-0.31 g butanol/g glycerol, Biebl, 2001). Lactic acid in the thin stillage acted as a buffering agent, maintaining the pH of the medium within a range of 5.7-6.1. Lactic acid was also utilized along with glycerol, enhancing butanol production (6.5 g/L butanol vs. 8.7 g/L butanol with 0 and 16 g/L lactic acid, respectively). These results demonstrate the feasibility of cost-effective butanol production using thin stillage as a nutrient-containing medium with a pH buffering capacity. (C) 2011 Elsevier Ltd. All rights reserved.